10 - The Food Security, Employment and Migration Nexus in Zimbabwe Post-land Reform: A Gender Perspective - Tekwa, Newman (Africa Development, 2022)
Serious inequalities in asset distribution in many developing countries consistently remain a key driver of household food insecurity, high unemployment, poverty and, ultimately, rural outmigration. Yet, the employment-retaining capacity of agriculture and its counter to rural-urban, including international, migration has been proven in many contexts. The 2000 land reform programme in Zimbabwe saw between 12 and18 per cent of women gaining access to land in their own right. Using a transformative social policy approach, the article explores the extent to which land reform as a social policy instrument enhanced household food security and rural incomes and opened new employment opportunities for beneficiaries relative to non-land reform beneficiary households. Highlighting the migration-social-policy nexus, I argue for land reform as a restraint to not only rural-urban but also international migration. Data gathered through a mixed methods ethnographic approach, combining in-depth interviews and surveys, and analysed using a combination of qualitative and quantitative methods, indicates that access to agricultural land and water can not only reduce but reverse rural to urban, including economically driven, international, migration. This suggests that continuous agrarianisation, in the Zimbabwean context, remains one plausible pathway to tackle the triple challenges of household food insecurity, unemployment and rural outmigration.